Preparation method of cross-linked porous nanofiber membrane for supercapacitor

The cross-linked porous nanofiber membrane prepared by electrospinning and cross-linking treatment solves the problems of low porosity and poor liquid absorption performance of the supercapacitor membrane, and achieves improved mechanical properties of the membrane and improved electrolyte exchange efficiency. It is suitable for high performance Preparation of supercapacitor diaphragm.

CN119145124APending Publication Date: 2024-12-17ANHUI POLYTECHNIC UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411284239.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The porosity of the existing supercapacitor diaphragms is low, the pore size and uneven distribution, and the liquid absorption and liquid retention performance are poor, resulting in unfast electrolyte ion exchange and large diaphragm thickness, which affects the reduction of the specific power and volume of the supercapacitor.

Method used

Polyacrylonitrile (PAN), high amylose (HAS) and polyvinylpyrrolidone (PVP) are used as the main materials to prepare cross-linked porous nanofiber membranes through electrospinning, hot pressing, pore making and cross-linking treatment to improve the pores of the membrane rate and mechanical properties.

Benefits of technology

It significantly improves the porosity, mechanical properties and hydrophilicity of the diaphragm, reduces the thickness of the diaphragm, and improves the specific capacitance and cycling stability of the supercapacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145124A_ABST
    Figure CN119145124A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nanofiber membranes, and relates to a preparation method of a cross-linked porous nanofiber membrane for a supercapacitor. Polyacrylonitrile (PAN) is adopted as a main material of the diaphragm, the stability of the diaphragm is improved, a water-soluble pore-forming agent PVP is added for pore-forming, the porosity of the diaphragm is improved, a natural material high-amylose starch is added, the prepared nanofiber membrane is reinforced through a cross-linking reaction of starch and glutaraldehyde, the mechanical property of the diaphragm is further improved, and the diaphragm can be used for preparing the diaphragm. The contact angle, the mechanical strength, the porosity and the thickness of the nanofiber membrane are controlled by adjusting the preparation process, so that the preparation of the high-performance supercapacitor diaphragm is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanofiber membranes, and in particular to a method for preparing a cross-linked porous nanofiber membrane for a supercapacitor. Background Art

[0002] The rapid development of the global economy has led to a significant increase in human demand for electrochemical energy storage devices (such as batteries, fuel cells, photovoltaic cells and supercapacitors). However, the life of traditional battery energy storage devices is much shorter than that of supercapacitors, and they pollute the environment. Supercapacitors have been deeply studied and widely concerned in energy storage devices due to their unique performance characteristics. As one of the important components of supercapacitors, diaphragms directly affect the specific power, specific capacity and cycle life of supercapacitors. Supercapacitor diaphragms mainly include cellulose paper diaphragms, synthetic polymer diaphragms, non-woven fabric diaphragms and biological diaphragms.

[0003] The material used for cellulose paper separator is cellulose fiber. During the paper-making process, a three-dimensional network structure is formed between the fibers. The microfibrils formed by fiber fibrillation form bridges between the main fibers and the microfibrils, making the paper have higher mechanical strength. However, the strength of a single fiber pulp paper separator product is not as good as that of a high molecular polymer separator formed by dry stretching, and the porosity, pore distribution uniformity, pore size and thickness of the separator need to be improved.

[0004] The electrical performance of supercapacitors made of synthetic polymer membranes is comparable to that of cellulose paper membranes, and the self-discharge rate is low. However, due to the low melting point of olefin polymers, the thermal stability of the membrane products is poor. In addition, due to the limitations of the production process and its own materials, it is difficult to further increase the porosity of polymer membranes and reduce the thickness while ensuring the safety performance of supercapacitors, which limits the further development of supercapacitors towards high power density, high energy density and smaller volume.

[0005] Non-woven fabric diaphragms have their unique advantages in the application of supercapacitors, but there are still major deficiencies in the preparation technology. Nanofiber membranes prepared using electrostatic spinning technology also belong to non-woven fabric diaphragms. Since non-woven fabric diaphragms are spun using electrostatic spinning equipment, the solvent evaporates during the spinning process, causing more charges to accumulate on the fiber surface, resulting in unstable spinning, which directly leads to deviations in the size and structure of the diaphragm, reducing the safety performance of the supercapacitor. The materials used to make the diaphragm have poor hydrophilicity, which makes it impossible for the electrolyte ions of the produced supercapacitor to be exchanged quickly during operation, affecting the improvement of specific power. Therefore, the large-scale application of non-woven fabric diaphragms in supercapacitors requires further improvement in their manufacturing process.

[0006] The biggest advantage of biological membranes compared to synthetic polymer membranes and non-woven fabric membranes is that the raw materials are green and environmentally friendly and have a wide range of sources. However, due to production and its own performance limitations, it is currently impossible to achieve industrial application.

[0007] In summary, the diaphragms currently used in supercapacitors mainly face the following problems: (1) The porosity of the diaphragm products is low, and the pore size and distribution are uneven; (2) Some diaphragms have poor liquid absorption and retention properties and cannot ensure the rapid exchange of electrolyte ions; (3) The diaphragm products are generally thicker, which hinders the reduction of the volume of the supercapacitor and increases the impedance of the diaphragm, thereby increasing the self-discharge. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing a cross-linked porous nanofiber membrane for a supercapacitor, so as to solve the problems existing in the above-mentioned prior art, improve the mechanical properties, porosity and hydrophilicity of the membrane, and reduce the thickness of the membrane.

[0009] To achieve the above object, the present invention provides the following solutions:

[0010] One of the technical solutions of the present invention is to provide a method for preparing a cross-linked porous nanofiber membrane for a supercapacitor, the steps comprising:

[0011] Polyacrylonitrile (PAN) is used as a polymer, high amylose starch (HAS) is used as a reinforcing material, polyvinyl pyrrolidone (PVP) is used as a pore-forming agent, and the mixture is mixed with a solvent to prepare a spinning solution;

[0012] The spinning solution is subjected to electrospinning to prepare an electrospinning membrane;

[0013] The electrospinning membrane is subjected to heat pressing treatment, pore making treatment and cross-linking treatment to obtain the cross-linked porous nanofiber membrane.

[0014] Furthermore, the mass ratio of PAN, HAS and PVP is 5-10:0-5:0-5, and the mass of HAS and PVP is not zero.

[0015] Furthermore, the solvent is dimethyl sulfoxide (DMSO).

[0016] Furthermore, the concentration of the spinning solution is 10-15wt%.

[0017] Furthermore, the electrospinning parameters are: temperature 30-45°C, relative humidity 40%, spinning voltage 10-20 kV, spinning distance 10-18 cm, drum speed 250 rpm, propulsion speed 0.5-2 mL / h, and spinning time 6-12 h.

[0018] Furthermore, the temperature of the hot pressing treatment is 50-80°C.

[0019] The hot pressing treatment of the present invention can be carried out using a small laboratory plastic sealing machine.

[0020] Furthermore, the pore making treatment is soaking in water for 4 to 10 hours.

[0021] Furthermore, the cross-linking treatment is performed using glutaraldehyde as a cross-linking agent and glutaraldehyde vapor for 2 to 8 hours.

[0022] Furthermore, the mass ratio of glutaraldehyde to HAS is 10-125:1.

[0023] The second technical solution of the present invention is to provide a cross-linked porous nanofiber membrane obtained by the above preparation method.

[0024] The third technical solution of the present invention is to provide an application of the above-mentioned cross-linked porous nanofiber membrane as a diaphragm in a supercapacitor.

[0025] The present invention discloses the following technical effects:

[0026] The present invention adopts polyacrylonitrile (PAN) as the main material of the diaphragm to improve the stability of the diaphragm, adds a water-soluble pore-forming agent PVP to form pores to improve the porosity of the diaphragm, adds a natural material high-amylose starch, and reinforces the prepared nanofiber membrane through the cross-linking reaction of starch and glutaraldehyde to further improve the mechanical properties of the diaphragm. The contact angle, mechanical strength, porosity and thickness of the nanofiber membrane are controlled by adjusting the preparation process to achieve the preparation of high-performance supercapacitor diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is the SEM image of the fiber membrane prepared in Example 1;

[0029] Figure 2 This is a SEM image of the fiber membrane prepared in Example 2;

[0030] Figure 3 This is a SEM image of the fiber membrane prepared in Example 3;

[0031] Figure 4 This is a SEM image of the fiber membrane prepared in Example 4;

[0032] Figure 5This is the SEM image of the fiber membrane prepared in Comparative Example 1;

[0033] Figure 6 This is the SEM image of the fiber membrane prepared in Comparative Example 2;

[0034] Figure 7 This is the SEM image of the fiber membrane prepared in Comparative Example 3;

[0035] Figure 8 The constant current charge-discharge curve and cyclic voltammetry curve of Comparative Example 1, wherein a is the constant current charge-discharge curve and b is the cyclic voltammetry curve;

[0036] Fig. 9 The constant current charge-discharge curve and cyclic voltammetry curve of Example 4, wherein a is the constant current charge-discharge curve and b is the cyclic voltammetry curve;

[0037] Fig.10 The constant current charge-discharge curve and cyclic voltammetry curve of Example 3, wherein a is the constant current charge-discharge curve and b is the cyclic voltammetry curve;

[0038] Fig.11 The constant current charge-discharge curve and cyclic voltammetry curve of Example 2, wherein a is the constant current charge-discharge curve and b is the cyclic voltammetry curve;

[0039] Fig.12 The constant current charge-discharge curve and cyclic voltammetry curve of Example 1, wherein a is the constant current charge-discharge curve and b is the cyclic voltammetry curve;

[0040] Fig.13 The AC impedance curves of Examples 1 to 4 and Comparative Example 1;

[0041] Fig.14 The cycle stability of Examples 1 to 4 and Comparative Example 1. DETAILED DESCRIPTION

[0042] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0043] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0044] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0045] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0046] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0047] Example 1

[0048] Preparation of cross-linked porous nanofiber membrane:

[0049] S1. PAN, HAS and PVP were mixed with a solvent (DMSO, analytical grade) in a mass ratio of 5:4:1 to prepare a spinning solution with a concentration of 12 wt%;

[0050] S2, using an electrospinning method, spinning for 8 hours at a temperature of 38.6°C and a relative humidity of 40%, with a spinning voltage of 15 kV, a spinning distance of 15 cm, a drum speed of 250 rpm, and a propulsion speed of 1 mL / h to obtain an electrospinning membrane;

[0051] S3, hot pressing the electrospun membrane using a hot press (70° C.) to obtain a hot pressed membrane;

[0052] S4, soaking the hot pressed film in deionized water for 8 hours to dissolve the PVP in the hot pressed film, and letting it stand and dry to obtain a pore-forming film;

[0053] S5. At room temperature, the porous membrane is placed in a vacuum pump and cross-linked with glutaraldehyde vapor for 5 hours to obtain a cross-linked porous nanofiber membrane, wherein the usage ratio of glutaraldehyde to HAS is 125:4.

[0054] Example 2

[0055] Compared with Example 1, the only difference is that the mass ratio of PAN, HAS and PVP is 5:3:2.

[0056] Example 3

[0057] Compared with Example 1, the only difference is that the mass ratio of PAN, HAS and PVP is 5:2:3.

[0058] Example 4

[0059] Compared with Example 1, the only difference is that the mass ratio of PAN, HAS and PVP is 5:1:4.

[0060] Comparative Example 1

[0061] Compared with Example 1, the only difference is that the mass ratio of PAN, HAS and PVP is 10:0:0.

[0062] Comparative Example 2

[0063] Compared with Example 1, the only difference is that the mass ratio of PAN, HAS and PVP is 5:0:5.

[0064] Comparative Example 3

[0065] Compared with Example 1, the only difference is that the mass ratio of PAN, HAS and PVP is 5:5:0.

[0066] Test example

[0067] The fiber membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were characterized by SEN. Figures 1 to 7 shown.

[0068] Figure 1 This is the SEM image of the fiber membrane prepared in Example 1; Figure 2 This is a SEM image of the fiber membrane prepared in Example 2; Figure 3 This is a SEM image of the fiber membrane prepared in Example 3; Figure 4 This is a SEM image of the fiber membrane prepared in Example 4; Figure 5 This is the SEM image of the fiber membrane prepared in Comparative Example 1; Figure 6 This is the SEM image of the fiber membrane prepared in Comparative Example 2; Figure 7 This is the SEM image of the fiber membrane prepared in Comparative Example 3. Figures 1 to 7 By comparison, the pure PAN nanofiber membrane prepared in Comparative Example 1 has a typical non-woven structure with randomly distributed fibers. After adding HAS and undergoing dissolution and cross-linking treatments, the fibers are bent, and the contact between the fibers is closer, with cross-linking points appearing. This indicates that a reaction occurs between starch and glutaraldehyde to produce a cross-linked structure between the fibers.

[0069] The mechanical properties of the hot pressed films, pore-forming films and fiber films prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were tested, and the results are shown in Table 1. The ratios in Table 1 are the mass ratios of PAN, HAS and PVP in Examples 1 to 4 and Comparative Examples 1 to 3.

[0070] Table 1 Stress-strain data table

[0071]

[0072] It can be seen from the data in Table 1 that the tensile strength of the hot-pressed film prepared at the ratio of 10:0:0 in Comparative Example 1 is 26.49-29.76MPa, and the elongation at break is 31.56-33.48%. The strength is slightly reduced after the pore-making treatment (immersion in water), and then the strength is slightly increased after the glutaraldehyde treatment. When the pore-forming agent PVP is added (5:0:5 in Comparative Example 2), the strength and elongation at break of the nanofiber membrane are greatly reduced. When HAS is added (5:5:0 in Comparative Example 3), the strength of the hot-pressed film is greatly improved, but the elongation at break is significantly reduced. The elongation at break of the pore-making film after the pore-making treatment increases significantly, and the elongation at break of the fiber membrane treated by cross-linking is greatly improved. The above results show that after cross-linking with glutaraldehyde, the mechanical properties of the nanofiber membrane containing HAS are improved.

[0073] The contact angles of the hot pressed films, pore-forming films and fiber films prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were analyzed and tested, and the results are shown in Table 2. The ratios in Table 2 are the mass ratios of PAN, HAS and PVP in Examples 1 to 4 and Comparative Examples 1 to 3.

[0074] Table 2 Contact angle data table

[0075]

[0076] As can be seen from Table 2, the contact angle of the hot-pressed film prepared at a ratio of 10:0:0 is as high as 140.44°, and the contact angle is significantly reduced after pore-making and cross-linking treatments. Compared with the embodiments and comparative examples of other ratios, the contact angle is significantly reduced after adding HAS and PVP, and the contact angles of the hot-pressed film mixed with the three materials are reduced after pore-making and cross-linking treatments, indicating that the fiber membrane modified by pore-making and cross-linking treatments has good water affinity. The better the hydrophilicity of the diaphragm, the better its effective contact with the electrolyte, which is more conducive to the permeation of ions in the electrolyte.

[0077] The thickness of the hot pressed films, pore-forming films and fiber films prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were analyzed and tested, and the results are shown in Table 3. The ratios in Table 3 are the mass ratios of PAN, HAS and PVP in Examples 1 to 4 and Comparative Examples 1 to 3.

[0078] Table 3 Thickness data table

[0079]

[0080]

[0081] It can be seen from Table 3 that with the addition of PVP, the thickness of the hot-pressed film becomes significantly smaller, while after adding HAS, the thickness of the hot-pressed film increases. After pore making or cross-linking treatment, the thickness of the fiber membrane is lower than that of the hot-pressed film.

[0082] The porosity of the fiber membranes prepared in Examples 1-4 and Comparative Examples 1-3 was analyzed and tested, and the results are shown in Table 4. The ratios in Table 4 are the mass ratios of PAN, HAS and PVP in Examples 1-4 and Comparative Examples 1-3.

[0083] Table 4 Porosity data table

[0084]

[0085] As shown in Table 4, the porosity of the fiber membrane prepared at a ratio of 10:0:0 is 42.197-48.358%. After adding PVP and HAS and undergoing pore-making and cross-linking treatments, the porosity of the fiber membrane is improved, reaching up to 99.265% (5:3:2).

[0086] Carbon fabric was used as an electrode and cut into a size of 1 cm×1 cm. The fiber membranes prepared in Examples 1 to 4 and Comparative Example 1 were used as diaphragms and cut into a size of 1.5 cm×1.5 cm. They were assembled into a symmetrical supercapacitor with a sandwich structure. The electrolyte was a 2 mol / l potassium hydroxide aqueous solution. Electrochemical tests were then performed, including constant current charge and discharge (GCD), cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS).

[0087] Cyclic stability test: The GCD method was used to continuously charge and discharge 5000 times at a current density of 1A / g to evaluate its stability.

[0088] Figure 8 The constant current charge-discharge curve and cyclic voltammetry curve of Comparative Example 1, wherein a is the constant current charge-discharge curve and b is the cyclic voltammetry curve; Fig. 9 The constant current charge-discharge curve and cyclic voltammetry curve of Example 4, wherein a is the constant current charge-discharge curve and b is the cyclic voltammetry curve; Fig.10 The constant current charge-discharge curve and cyclic voltammetry curve of Example 3, wherein a is the constant current charge-discharge curve and b is the cyclic voltammetry curve; Fig.11 The constant current charge-discharge curve and cyclic voltammetry curve of Example 2, wherein a is the constant current charge-discharge curve and b is the cyclic voltammetry curve; Fig.12The constant current charge-discharge curve and the cyclic voltammetry curve of Example 1, wherein a is the constant current charge-discharge curve and b is the cyclic voltammetry curve; Figures 8 to 12 It can be concluded that the specific capacitance of the supercapacitor is 21.03 F / g (Comparative Example 1), 14.05 F / g (Example 2), 1.55 F / g (Example 3), 16.47 F / g (Example 4) and 26.05 F / g (Example 1) at a current density of 0.25 A / g.

[0089] Fig.13 are the AC impedance curves of Examples 1 to 4 and Comparative Example 1; Fig.13 It can be obtained that the internal resistance of the supercapacitor is 1.14Ω (Comparative Example 1), 1.04Ω (Example 2), 1.39Ω (Example 3), 1.8Ω (Example 4) and 0.95Ω (Example 1).

[0090] Fig.14 The cycle stability of Examples 1 to 4 and Comparative Example 1 is Fig.14 It can be seen that after 5000 consecutive charge and discharge cycles, the specific capacitance retention rates are 91.56% (Comparative Example 1), 93.43% (Example 2), 92.03% (Example 3), 91.09% (Example 2) and 94.36% (Example 1), respectively.

[0091] Table 5 Specific capacitance data table

[0092]

[0093] The specific capacitance retention rate is the ratio of the specific capacitance corresponding to 2 A / g to the specific capacitance corresponding to 0.25 A / g.

[0094] The specific capacitance of the supercapacitor device was obtained through electrochemical testing. The device composed of the fiber membrane prepared with a mass ratio of PAN, HAS and PVP of 5:4:1 as a diaphragm in Example 1 had a maximum specific capacitance of 26.05 F / g, a current density of 0.25 A / g, and a specific capacitance retention rate of up to 47% at 2 A / g.

[0095] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a cross-linked porous nanofiber membrane for supercapacitors, characterized in that the steps include: PAN is used as a polymer, HAS is used as a reinforcing material, PVP is used as a pore-forming agent, and the mixture is mixed with a solvent to prepare a spinning solution; The spinning solution is subjected to electrospinning to prepare an electrospinning membrane; The electrospinning membrane is subjected to heat pressing treatment, pore making treatment and cross-linking treatment to obtain the cross-linked porous nanofiber membrane.

2. The preparation method according to claim 1, characterized in that: The mass ratio of PAN, HAS and PVP is 5-10:0-5:0-5, and the mass of HAS and PVP is not zero.

3. The preparation method according to claim 1, characterized in that: The solvent is dimethyl sulfoxide.

4. The preparation method according to claim 1, characterized in that: The concentration of the spinning solution is 10-15 wt %.

5. The preparation method according to claim 1, characterized in that: The electrospinning parameters are: temperature 30-45°C, relative humidity 40%, spinning voltage 10-20 kV, spinning distance 10-18 cm, drum speed 250 rpm, propulsion speed 0.5-2 mL / h, and spinning time 6-12 h.

6. The preparation method according to claim 1, characterized in that: The temperature of the hot pressing treatment is 50-80°C.

7. The preparation method according to claim 1, characterized in that: The pore making process is to soak in water for 4 to 10 hours.

8. The preparation method according to claim 1, characterized in that: The cross-linking treatment uses glutaraldehyde as a cross-linking agent and adopts glutaraldehyde vapor to perform cross-linking treatment for 2 to 8 hours; the mass ratio of glutaraldehyde to HAS is 10 to 125:

1.

9. A cross-linked porous nanofiber membrane prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the cross-linked porous nanofiber membrane as claimed in claim 9 as a separator in a supercapacitor.

Citation Information

Patent Citations

  • Preparation methods of porous carbon nanofiber felt and porous carbon nanofiber electrode

    CN104342852A

  • Preparation method of porous graphene nanofiber membrane

    CN105483939A

  • Polyacrylonitrile fibre film material being of netted porous structure, and preparation method and application thereof

    CN106948089A

  • Carbon nanofiber felt with porous interconnection structure as well as preparation method and application of carbon nanofiber felt

    CN113668140A

  • 3D polymer nanofiber membrane composed of 1d individual polymer nanofibers which are quasi-aligned and cross-laminated like grid structure with functions of controlling pore distribution and size, and manufacturing method thereof

    US20180015423A1